Government Strategic Collaborative Partnership in Tourism Affairs A Study in Malang and Batu City Governments - Hevi Kurnia Hardini (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2018)
Tourism is defined as part of government affairs related to public services in whichconcerning cross-regional externalities, therefore, its implementation are based on efficiencies that can be managed collaboratively. However, the rapid-demanding needs of tourism, force each region to partially fulfill their needs with short-term political orientation. This research would like to investigate the identification of the tourism potentials in the form of collaborative partnership between Malang and Batu governments and finding out the model of strategic tourism partnership between Malang and Batu governments. The qualitative methods with descriptive research type are applied to this research. The primary data collection technique was conducted by observation, structured-interview with related government institutions, experts and also related stakeholders. While the secondary data collection was done through documentation and bibliography techniques. Research subject was determined by using purposive sampling technique. Tourism potentials in Malang and Batu Cities offer their own strategic attraction in East Java that is complementary to each other. This study revealed that the tourism potentials are still not yet developed in the official scheme of partnership by the Malang and Batu local governments. This study offers the appropriate model of cooperation for the existing condition of each local government. Specifically, a specific cooperation on tourism affairs with the form of Cooperative Construction of procurement of physical buildings between tourist destinations in both regions is hereby discussed. Thus, the persistent problem of traffic congestion resulting from the rapid development of tourism can be addressed together effectively and efficiently. In addition, the Joint Services cooperation model can be done by both parties by establishing a one-stop service as a tourist information center of both cities.